North Platte River Basin wetland profile and condition assessment - Lemly, Joanna M., author; Gilligan, Laurie, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2012)
This report summarizes finding from the second basinwide wetland condition assessment, conducted in the North Platte River Basin. The initial step in each project is to compile a "wetland profile" based on digital wetland mapping. Wetland profiles summarize the types, abundance, and distribution of wetlands among ecoregions and landownership within a given geographic area and can be used to establish baseline conditions, assess cumulative impacts, and inform conservation planning. The second step in each project is to conduct a field-based assessment of ecological condition and associated stressors that can be extrapolated to all wetland area in the basin. Assessing the ecological condition of wetlands within each basin provides a coarse filter for prioritizing on-the-ground efforts to protect and restore wetland habitat. Through this project, CPW and CNHP developed a wetland profile of the North Platte River Basin to document the spatial distribution of wetlands, conducted a field-based assessment of wetland condition, and used the data to estimate both overall condition of wetlands and the availability of wetland habitat across the basin.
Prepared for: Colorado Parks and Wildlife Wetland Wildlife Conservation Program, U.S. Environmental Protection Agency, Region 8.
Keywords: Colorado; waterfowl; wildlife; watershed management; wetlands monitoring; wetland ecology